Rethinking Sustainable Development Drivers in D-8 Countries: Markets, Global Integration, and Political Constraints - Amirullah, Malik Abd. Karim; Kamaluddin, Kamaluddin; Wibowo, Muhammad Ghafur; Ihsan, Akmal; Ghannili, Farawi (Universitas Pasundan, 2025)
Sustainable development in D-8 countries remains limited by structural economic disparities and shifting political conditions. Using dynamic panel data from 2010–2019 with a GMM approach, this study evaluates how foreign direct investment, industrialization, de jure globalization, digitalization, economic growth, corruption control, and domestic credit shape SDG performance, with political constraints as a moderator. The results show that foreign investment, industrialization, globalization, and digitalization enhance SDGs, while domestic credit hinders them. Political constraints reduce the impact of foreign investment yet strengthen the role of economic growth. The findings underscore the need for political stability and disciplined credit management to support progress.